2015
DOI: 10.15740/has/vsrj/6.2/71-79
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid protein profile in buffalo

Abstract: : The present study was planned to investigate and compare the protein profile viz. total proteins, albumin, globulin, albumin/globulin ratio, uric acid, urea and creatinine in follicular fluid and serum in buffaloes. The electrophoretic pattern of proteins in follicular fluid of different sizes of ovarian follicles and serum were also studied. Buffalo ovaries, at random stage of oestrous cycle and with unknown reproductive status were obtained from Deonar Abattoir, Chembur, Mumbai, during their e-visceration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The follicle size-dependent increase of estradiol was in agreement with previous studies primate human [45] and non-human [46], rat [47] and livestock [48, 49], reporting association between estradiol synthesis and follicular cell viability. In contrast, intrafollicular protein concentrations were comparable regardless of their origins, and were consistent with previous findings in pigs [50], cows [51], buffaloes [52], and goats [13].…”
Section: Discussionsupporting
confidence: 91%
“…The follicle size-dependent increase of estradiol was in agreement with previous studies primate human [45] and non-human [46], rat [47] and livestock [48, 49], reporting association between estradiol synthesis and follicular cell viability. In contrast, intrafollicular protein concentrations were comparable regardless of their origins, and were consistent with previous findings in pigs [50], cows [51], buffaloes [52], and goats [13].…”
Section: Discussionsupporting
confidence: 91%
“…Maniwa et al (2005) used 2-D PAGE and MALDI-TOF MS to detect differentially expressed proteins in bovine ovarian follicular cysts and healthy cow FF. Joy et al (2015) used proteomics to detect the protein expression of buffalo FF with follicles of different sizes. Zachut et al (2016) identified 219 proteins in cow FF and showed 8 DEPs were associated with follicular development in the FF of less fertile cows and healthy dairy cows.…”
Section: Introductionmentioning
confidence: 99%